A void fraction of high-viscosity air-water flow in capillary pipes with a slope of 30 degrees to the horizontal positio - Sukamta Sukamta; Metra Prayogi Rianda; Sudarja Sudarja (Universitas Muhammadiyah Metro, 2019)
Two-phase flow is a flow that is composed of several combined substances, namely liquid and gas. Two-phase flow is found in industrial processes, such as in boiler systems, reactors, heat exchangers, geothermal and others. The phenomenon of two-phase flow is also often found in nature, such as fog, snow, clouds, and rain. The purpose of this study was to obtain the characteristics, length, and frequency of flow patterns in two phases based on the experimental value of the fraction in a two-phase flow of a mixture of water-glycerin and air in a capillary tube with a slope of 30˚. The study used a 1.6 mm diameter capillary tube with a working fluid which mixed air and water mixed with glycerin with glycerin concentrations of 40%, 50%, 60%, and 70%. Void fraction values were analyzed using digital image processing methods with the MATLAB R2014a application program. The results showed that the void fraction value was determined by the surface velocity of the liquid and air. The greater the superficial air velocity, the value of the vacuum fraction will develop, while the greater the superficial velocity of the liquid, the vacuum fraction will decrease. The flow pattern of bubbles and plugs is strongly influenced by fluid viscosity. Therefore the higher the viscosity, the velocity of the bubble and plug flow patterns will decrease, conversely if the viscosity of the fluid decreases, the velocity of the bubble and plug flow patterns will increase. The length and flow of the bubble pattern are strongly influenced by homogeneous values (β). If the homogeneous value (β) is higher then the length of the flow pattern will increase. In the stopper flow pattern obtained a high enough frequency, it will produce a high enough void fraction value. Keywords: Two-phase, fluid, void fraction, viscosity, flow pattern.